The God of the Left Hemisphere Blake, Bolte Taylor and the Myth of Creation. - Tweedy, Roderick (London : Karnac Books, 2013)
The God of the Left Hemisphere explores the remarkable connections between the activities and functions of the human brain that writer William Blake termed 'Urizen' and the powerful complex of rationalising and ordering processes which modern neuroscience identifies as 'left hemisphere' brain activity. The book argues that Blake's profound understanding of the human brain is finding surprising corroboration in recent neuroscientific discoveries, such as those of the influential Harvard neuro-anatomist Jill Bolte Taylor, and it explores Blake's provocative supposition that the emergence of thes.
APPENDIX The symbolism of left and right in Blake's workNOTES; REFERENCES; INDEX.
Description based on print version record.
Keywords: Cerebrovascular disease -- Patients -- United States; Mind-Body Relations, Metaphysical; Taylor, Jill Bolte, 1959- -- Health; Taylor, Jill Bolte, 1959-; Blake, William, -- 1757-1827.; Blake, William, -- 1757-1827 -- Criticism and interpretation; Taylor, Jill Bolte, -- 1959- -- Health; Metaphysics; Creation; God; Myth; SCIENCE / Cognitive Science; Electronic books